2005
DOI: 10.1002/ptr.1660
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Curcuma longa L. against methicillin‐resistant Staphylococcus aureus

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) has been emerging worldwide as one of the most important hospital and community pathogens. Therefore, new agents are needed to treat MRSA associated infections. The present study investigated the antimicrobial activity of ethyl acetate, methanol and water extracts of Curcuma longa L. (C. longa) against MRSA. The ethyl acetate extract of C. longa demonstrated a higher antibacterial activity than the methanol extract or water extract. Since the ethyl acetate ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 24 publications
4
43
0
2
Order By: Relevance
“…Antimicrobial resistance is resulting in increased morbidity, mortality and health-care costs. The discovery and development of potent and nontoxic, antimicrobial agents has thus become an important scientific challenge (Natarajan et al, 2003;Weigel et al, 2003;Kim et al, 2005). Plants synthesize chemicals as part of their defense against pathogens.…”
Section: Introductionmentioning
confidence: 98%
“…Antimicrobial resistance is resulting in increased morbidity, mortality and health-care costs. The discovery and development of potent and nontoxic, antimicrobial agents has thus become an important scientific challenge (Natarajan et al, 2003;Weigel et al, 2003;Kim et al, 2005). Plants synthesize chemicals as part of their defense against pathogens.…”
Section: Introductionmentioning
confidence: 98%
“…In the present study, analyses of growth inhibition activity performed by using the well diffusion method showed that all the tested plants, which are commonly used by traditional medical practitioners, exhibited moderate activity against clinical isolates of bacterial strains at extract concentrations of 1 mg/ml Nitta et al, 2002;Voravuthikunchai and Kitpipit, 2005). Infections caused by multiple drug resistance, including resistance to β-lactam, are among the most difficult infections to treat (Abu-Shanab et al, 2004, 2006Kim et al, 2005). In this study, the growth of S. aureus, E. coli, K. pneumoniae, S. typhi and A. baumannii were markedly inhibited by some extracts of D.…”
Section: Discussionmentioning
confidence: 64%
“…Multiple drug resistant (MDR) pathogens has been increasing, causing nosocomial and communityacquired deadly infections mainly due to the extensive utilization of antibiotics (Köck et al, 2010;Mongalo et al, 2013). Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella typhi and Acinetobacter baumannii have inherent resistant to most available antibiotics (Chambers, 1997;Kim et al, 2005;Patzer and Dzierzanowska, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new agents are needed to treat MRSA associated infection. To meet this need, plant extracts have been screened for activity against strains of MRSA (Hur et al, 2004;Kim et al, 2004Kim et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%